2015
DOI: 10.1128/mbio.01305-15
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum orbiculare FAM1 Encodes a Novel Woronin Body-Associated Pex22 Peroxin Required for Appressorium-Mediated Plant Infection

Abstract: The cucumber anthracnose fungus Colletotrichum orbiculare forms specialized cells called appressoria for host penetration. We identified a gene, FAM1, encoding a novel peroxin protein that is essential for peroxisome biogenesis and that associates with Woronin bodies (WBs), dense-core vesicles found only in filamentous ascomycete fungi which function to maintain cellular integrity. The fam1 disrupted mutants were unable to grow on medium containing oleic acids as the sole carbon source and were nonpathogenic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Both the deletion and overexpression of FgHex1 in F. graminearum reduced fungal infectivity [ 19 ]. However, intriguingly, the deletion of CoHex1 in the cucumber anthracnose fungus Colletotrichum orbiculare did not produce any detectable defects in appressorium formation and infectivity [ 42 ]. This kind of species-dependent phenotypic diversity of Hex1 deletion mutants indicates again the functional alterations of this conserved gene in different fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Both the deletion and overexpression of FgHex1 in F. graminearum reduced fungal infectivity [ 19 ]. However, intriguingly, the deletion of CoHex1 in the cucumber anthracnose fungus Colletotrichum orbiculare did not produce any detectable defects in appressorium formation and infectivity [ 42 ]. This kind of species-dependent phenotypic diversity of Hex1 deletion mutants indicates again the functional alterations of this conserved gene in different fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, filamentous ascomycetes have a specific peroxin, Pex22-like, which shows low homology to Pex22 in S. cerevisiae but contains a typical Pex4-binding domain conserved in Pex22 proteins [27]. Fam1, the Pex22-like protein in C. orbiculare, has been shown to be able to complement the defect in peroxisomal matrix import of S. cerevisiae pex22 mutants [57]. fam1 mutants are incapable of importing PTS-containing proteins and are defective in peroxisome function and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In M. oryzae , deletion of Hex1 showed that WBs are required not only for appressorial morphogenesis but also for invasive growth in plants by enhancing resistance to nutritional stress (Soundararajan et al, 2004 ). WBs are distributed at the hyphal tips and septa (Kubo et al, 2015 ). Currently, we do not know the significance of the hyphal tip‐localized WBs and the mechanism of how WBs are distributed at the hyphal tip.…”
Section: Discussionmentioning
confidence: 99%
“…WBs are distributed at the hyphal tips and septa (Kubo et al, 2015). Currently, we do not know the significance of the hyphal tip-localized WBs and the mechanism of how WBs are distributed at the hyphal tip.…”
Section: Motwf Is Required For the Distribution Of Mohex1 At The Hyphal Tipmentioning
confidence: 99%